The Cuban Revolution in the 21st century - Lambie, George (Pluto Press, 2010)
While most writing on Cuba seeks to analyse the island's socialist experiment from the perspective of either its internal dynamics or international relations, this book attempts to understand the revolutionary process as part of a counter-current against neoliberal globalisation. Now that neoliberalism is in crisis, Cuba's promotion of socialist values is finding a renewed relevance.